Bovine leukemia virus transmission rates in persistent lymphocytotic infected dairy cows - Benavides, Bibiana; Monti, Gustavo (Frontiers in Veterinary Science, 2024)
Bovine leukemia virus (BLV) establishes a lifelong persistent infection in dairy cattle. White blood cell count (WBC) is correlated with proviral load in the blood and milk of BLV-infected cattle, and testing WBC can be used to assess both BLV infectiousness levels and risk of BLV transmission from different types of infected animals. The objective of the study was to compare effective transmission rates () and the basic reproduction ratio (Ro) among two types of BLV-infected dairy cows in Chile: those affected with persistent lymphocytosis (PL) versus aleukemic (AL). The estimated () coefficient was higher in PL cattle (1.1; 95% Confidence interval (CI) (-1.6, 3.8), compared to AL cattle (-3.1; 95% CI = -3.7, -2.5). In addition, the Ro was higher in PL cattle (60.4; 95% CI = 3.5; 820.6), compared to AL cattle (1.5; 95% CI = 0.7, 3.1). The ratio between the PL/AL expected rate of cases was 73.9. The estimated effective transmission rate and the Ro were higher in PL cattle compared to AL cattle. The WBC test is a convenient alternative that can be considered for risk identification and risk management of BLV infection in dairy herds; particularly in livestock regions where laboratory capacity is limited (e.g., use of PCR or gene sequencing techniques) and/or molecular tests are not cost-effective. Therefore, when the prevalence of infection is high, the removal of PL cattle should be engaged to control BLV within-herds.